O. M. Afanasieva. Ritualized communicative practices in the age of new tecnologies - O. M. Afanasieva (Philological Treatises, 2020)
The article is devoted to the review and analysis of modern interpretations of the newest communication processes in the digital environment and identification of the main parameters and attributes of these processes which determine their ritualization. Cognitive, praxis, sociocommunicative and strictly communicative parameters of the organization of the virtual communication space are singled out. New signs and types of communicative structures, interactive models, communicative actors, forms and means of communication are presented. Communicative practices in the era of new technologies are considered in view of the interaction of the processes of routinization and ritualization, which lead to the consolidation of certain practices and attribute them a cultural and symbolic dimension. The ritual is considered in a dynamic aspect, which determines the possibilities of its transfer, transformations, etc.